EFFECT OF DIFFERENT AB MIX CONCENTRATIONS ON THE GROWTH AND YIELD OF SEVERAL MUSTARD VARIETIES IN AN AEROPONIC SYSTEM - Perkasa, Achmad Yozar; Arif Aula Rizki; Budiman; Zatanna Balqis (Universitas Trisakti, 2025)
The mustard plant is a vegetable that Indonesian people widely consume. This research analyzes differences in AB mix nutrient concentrations on the growth and yield of several mustard varieties in an aeroponic system. The research was conducted in the Greenhouse Smart Farming Gunadarma University Technopark (UG-TechnoPark) from March to June 2024. This research used the Nested Pattern Randomized Complete Group Design method (Nested Design), which consists of 2 factors. Factor I is the concentration of AB mix nutrients (K) consisting of 2 levels, which are 1200 ppm (K1) and 1800 ppm (K2). Factor II is the type of mustard variety (V) consisting of 4 levels, namely Kumala (V1), Shinta F1 (V2), Kometa (V3), and Tosakan (V4). The results showed that differences in AB mix nutrient concentrations have significantly affected the growth and yield of the mustard plant on some parameter, which is plant height, number of leaves, root length, and dry weight of plant canopy with the highest average values, respectively, which is 35.76 cm, 10.81 leaves, 19.84 cm, and 4.18 grams. The differences in varieties have a significant effect on the growth and yield of mustard plants on the parameters of plant height, number of leaves, leaf length, leaf width, shoot wet weight, shoot dry weight, and root dry weight with the highest average value respectively, which is 39.54 cm, 11.87 leaves, 17.39 cm, 10.85 cm, 69.13 grams, 4.98 grams, and 2.06 grams.